Autistic Traits and Executive Functions in Children and Adolescents With Gender Dysphoria - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
We aimed to examine the autistic traits and executive functions that may require clinical attention in children and adolescents with gender dysphoria (GD). The study sample consisted of 25 patients with GD and 50 controls (aged five to 17 years). The instruments were the Social Responsiveness Scale (SRS) and the Behavior Rating Inventory of Executive Function (BRIEF). The GD (mean age: 11.56 +/- 4.15 years) and control (mean age: 11.42 +/- 3.91 years) groups were similar with respect to age and sex; around 50% of the GD group (n = 13) and control groups were male (n = 26). The BRIEF metacognitive index (t = 7.023, p < 0.001), behavioral regulation index (t = 6.340, p < 0.001), and global executive composite (t = 7.268, p < 0.001) scores were significantly higher in the GD group when compared with the controls. Similarly, mean SRS scores were significantly higher in the GD group (t = 4.978, p < 0.001). The GD group had statistically significant higher BRIEF global scores even after controlling for SRS-key autism scores (p < 0.001). Young people with GD had relatively more disturbed behavior related to executive functions and social impairment associated with autistic traits when compared with their control counterparts. Although preliminary, our results may indicate a possible neurodevelopmental background for individuals with GD.
Keywords: SPECTRUM DISORDERS; TESTOSTERONE; ATTENTION; ANDROGENS; IDENTITY; FEATURES; BEHAVIOR; PEOPLE; SEX